Corporate social responsibility: Mapping its social meaning - Duarte, Ana Patrícia (2010)
Purpose – The purpose of this paper is to address the social meaning of corporate social responsibility (CSR) and improve understanding of this concept. Design/methodology/approach – A free association task was completed by a sample of 275 individuals, mostly employees from different industries, who were given “socially responsible corporation” as the stimulus. Findings – The results elicit three distinct views of a socially responsible corporation. Some individuals consider a socially responsible corporation to be one that undertakes its business operations in an efficient and ethical manner. Others see it as an organisation that takes an active role in contributing to the well being of society and behaves in an ecologically friendly way and acts in the field of social solidarity. For yet another set of participants a socially responsible corporation is one that adopts human resources practices that demonstrate respect and concern for the well being of employees and their families. Research limitations/implications – The social meaning of CSR includes ideas that to some extent mirror the conceptualisation introduced by previous theoretical models. However, this paper suggests that the translation of the theoretical models into instruments addressing stakeholders’ perceptions of CSR requires closer scrutiny and validation through contextual (e.g. national) adaptations. Originality/value – The paper contributes by providing additional knowledge on the social meaning of CSR in a European country, Portugal, and not only on Anglo-Saxon countries, therefore, introducing specific situational challenges.